Morphological, vascular, and functional changes in macular telangiectasia type 2 in Egyptian patients - Shaimaa Ibrahim Gafar; Hany Hamza; Ihab Abdelaziz; Rania G. Estawro; Shaymaa Hassan Salah (Scientific Reports, 2025)
Abstract Little documented studies regarding analysis of macular telangiectasia type 2 in Egyptian patients. This prospective study included 24 eyes with MacTel-2, and 24 control eyes. Spectral-domain optical coherence tomography Angiography (OCT-A) was performed. Staging of eyes with MacTel-2, quantification of Foveal and parafoveal vascular density and full retinal thickness were performed. In MacTel-2 eyes, the superficial capillary vessel density was significantly decreased in the temporal, superior and inferior para-foveal area (p-value = 0.004, < 0.001 and 0.002 respectively). Only temporal parafoveal deep vessel density showed significant decrease in the MacTel-2 group as compared with the normal control group (49.6% versus 54.01%, p value = 0.010). There was a statistically significant decrease in the foveal and all the para-foveal thickness as compared with normal control group (P < 0.001). One-fourth of cases were classified as stage 4 MacTel-2. The patterns of neovessels were sea-fan, tangled or dead tree network, equally distributed among the six affected eyes. A significant reduction in both foveal density and visual acuity was documented with disease progression. This study emphasizes the role of OCT-A in diagnosis, staging and identification of neovascular pattern of MacTel-2. Furethermore, this study is considered one of the few Egyptian studies in staging the disease providing correlation to visual acuity, macular thickness and vessel density affection.